Cardiac surgeryLong onlay bypass grafting using the left internal mammary artery for proximal and mid stenosis of the left anterior descending artery - Emrecan, Bilgin; Özdemir, Ahmet Coşkun; Alihanoğlu, Yusuf İzzettin; Kılıç, İsmail Doğu (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Aim of the study: According to the literature, many surgeons aim to obtain complete revascularization during coronary artery surgery. This becomes an issue when the left anterior descending (LAD) artery is diffusely diseased. This study presents the results of revascularization surgery of LAD arteries with multiple stenoses and the subsequent angiographic control examinations. Material and methods : Forty-seven patients with proximal and mid-segment left anterior descending (LAD) artery disease were included in the study. Left anterior descending arteries were bypassed with left internal mammary arteries (LIMAs). Left anterior descending arteries were longitudinally opened over the mid stenotic segments 4-5 mm distally and proximally from the stenosis. The LIMAs were then anastomosed to the LAD arteries with a running suture, using 7-0 polypropylene sutures. Thirteen patients, who provided their informed consent, were angiographically evaluated at a mean of 12.5 ±3.7 months after the operation (range 6-18 months). Results : The mean age of the patients was 64.1 ±8.9 years. The mean number of distal anastomoses was 3.5 ±0.9 (range 1-6). The mean length of LAD anastomoses was 1.88 ±0.54 cm (range 1.5-4 cm). Cardiac troponin I levels were below perioperative myocardial infarction thresholds. Mean postoperative hospitalization was 6.10 ±0.98 days (range 5-9 days). There was no mortality in the study group. Control angiography revealed patent bypass grafts in all patients. Conclusions: Long anastomosis to the LAD artery provides excellent mid-term patency. It is safe and effective in perfusing the proximal and distal non-stenotic segments of the LAD artery, as well as in perfusing the unoccluded side branches originating from the stenotic segments.